Exploring the Help-Seeking Attitudes of Graduate Students at an Off-Campus Site - McCarthy, John T.; Bruno, Michelle L.; Sherman, Christine A. (Canadian Journal of Counselling and Psychotherapy, 2010)
This study examined the help-seeking attitudes of graduate students enrolled in an off-campus professional centre. The sample consisted of 217 participants enrolled in 10 graduate programs (130 women [60%], 37 men [17%], 50 unspecified [23%]). Analyses (descriptive statistics and t-tests) indicated that women possessed more favourable at-titudes toward seeking counselling than men. Furthermore, an overwhelming majority of graduate students would not travel to the main campus to utilize counselling services. Many participants identified potential obstacles, including lack of time, affordability, and lack of insurance coverage, as important obstacles to help-seeking. Several factors were also found to be significant predictors of help-seeking attitudes. University counselling centre professionals are encouraged to be available and sensitive to the counselling needs of off-campus graduate students.